Intercambio de mercado y consolidación en el corazón del Imperio Azteca - Garraty, Christopher P. (Revista Española de Antropología Americana, 2007)
One important way that empires consolidate power is to undercut the traditional revenue bases of subject elites and redirect resource flows from subject areas to the imperial capitals. To this end, Aztec imperial rulers implemented a strategy to appropriate marketplace revenues from subject elites in the imperial heartland in the Basin of Mexico. Recent chemistry-based provenance studies of undecorated Aztec plainware and Blackon- orange vessels suggest that pottery made in the Tenochtitlan area penetrated market domains of neighboring polities, including their Acolhua allies in Texcoco. The imperial rulers in Tenochtitlan likely invested in marketplace development to stimulate commercial craft production and export, thus boosting government revenues from market taxation.